Crystallization behaviour of poly(ethylene oxide) under confinement in the electrospun nanofibers of polystyrene/poly(ethylene oxide) blends. Issue 23 (17th May 2016) - Samanta, Pratick; V., Thangapandian; Singh, Sajan; Srivastava, Rajiv; Nandan, Bhanu; Liu, Chien-Liang; Chen, Hsin-Lung
Abstract : We report on the confinement driven frustrated crystallization behavior of PEO in electrospun nanofibers of PS/PEO blends where PS was present as the major component. Abstract : We have studied the confined crystallization behaviour of poly(ethylene oxide) (PEO) in the electrospun nanofibers of the phase-separated blends of polystyrene (PS) and PEO, where PS was present as the major component. The size and shape of PEO domains in the nanofibers were considerably different from those in the cast films, presumably because of the nano-dimensions of the nanofibers and the extensional forces experienced by the polymer solution during electrospinning. The phase-separated morphology in turn influenced the crystallization behaviour of PEO in the blend nanofibers. At a PEO weight fraction of ≥0.3, crystallization occurred through a heterogeneous nucleation mechanism similar to that in cast blend films. However, as the PEO weight fraction in the blend nanofibers was reduced from 0.3 to 0.2, an abrupt transformation of the nucleation mechanism from the heterogeneous to predominantly homogenous type was observed. The change in the nucleation mechanism implied a drastic reduction of the spatial continuity of PEO domains in the nanofibers, which was not encountered in the cast film. The melting temperature and crystallinity of the PEO crystallites developed in the nanofibers were also significantly lower than those in the corresponding cast films. The phenomena observed were reconciled by the morphological observation, which revealed that the phase separation under the radial constraint of the nanofibers led to the formation of small-sized fibrillar PEO domains with limited spatial connectivity. The thermal treatment of the PS/PEO blend nanofibers above the glass transition temperature of PS induced an even stronger confinement effect on PEO crystallization.